Kajian Tvc Wonderful Indonesia sebagai Cermin Citra Indonesia di Mata Dunia - Angela Oscario (Bina Nusantara University, 2013)
Tourism is one of the most important sectors supporting the economy of Indonesia. One way to develop the Indonesian tourism is strengthening the image of Indonesia in the world. To strengthen the image, Indonesia has replaced the old brand, “Visit Indonesia”, and launched a new brand, “Wonderful Indonesia”. Besides the logo, in order to campaign “Wonderful Indonesia,” some television commercials have been launched. An advertising, which creates a powerful image, not only has a great power to influence the viewers but can also be a double-edged sword. Advertising can become a mirror of reality, but it can also become a distorted mirror of reality. A similar case happens with Wonderful Indonesia television commercial, which was released early in 2012 by the Ministry of Tourism and Creative Economy. The television commercial is considered to have distorted the image of Indonesia in the world by displaying only the culture, society, and nature of Java and Bali. Meanwhile, the other Wonderful Indonesia television commercial, “Feeling is Believing,” which was launched by Indonesia Tourism Board in 2012 considered to have become quite successful framing the beauty, and diversity of the cultures, communities, regions, and natures of Indonesia. Learning from the mistakes, and considering the importance of an image, the future Wonderful Indonesia television commercial should be dealt more carefully. The image that is proper to represent Indonesia, the visual signifier should reflect the intended signified precisely.